Peripheral artery disease in women - Yavuz, Senol; Özsin, Kadir; Sanrı, Umut Serhat; Toktaş, Faruk (The European Research Journal, 2020)
Peripheral artery disease (PAD) is a common disease among women and is expected to increase in the coming years. Diagnostic and therapeutic management of PAD in women is difficult due to their gender-related differences, comorbid factors, atypical symptoms, more functional disorders, the presence of advanced disease, being older age of the disease onset, smaller vessel diameter, and psychosocial factors. Especially due to the high prevalence of asymptomatic disease, late admission status and further disease on admission affect the success of the treatment negatively. By focusing more on PAD in women and more clinical studies, gender-specific differences can be identified. Hereby, there is a need to develop appropriate strategies to improve women’s overall quality of life. In this review, we aimed to draw attention to the female gender with PAD, which is increasingly occurring.